Investigation of beta-glucan activity in honey bees (Apis mellifera) infected with Nosema ceranae - Tatli Seven, Pinar; Iflazoglu Mutlu, Seda; Turhalli, Ceyda; Kilic, Fulya; Aslan, Abdullah; Elbir, Nurgul; Seven, Ismail (Taylor & Francis Ltd, 2025)
Nosema ceranae is a microsporidian parasite that infects the midgut epithelial cells of honey bees (Apis mellifera), causing digestive dysfunction, reduced lifespan, impaired foraging activity and flight performance, and ultimately leading to declines in colony population and productivity. The emergence of resistance to conventional treatments such as fumagillin highlights the need for sustainable and effective alternative control strategies. This study aimed to evaluate the effects of beta-glucan supplementation on food consumption, survival rate, spore load, and antioxidant status in N. ceranae-infected honey bees. A total of 1000 newly emerged, disease-free worker bees (0-3 days old) were randomly allocated into five experimental groups, each comprising four replicates with 50 bees. All bees were provided with a 50% (w/v) sucrose solution ad libitum. The experimental groups were designated as follows: Control (uninfected), N (Nosema-infected,105 spores/bee), BG0.5 (0.5% beta-glucan, uninfected), N + BG0.5 (Nosema-infected + 0.5% beta-glucan), and N + BG1 (Nosema-infected + 1% beta-glucan). Beta-glucan supplementation resulted in a marked reduction in spore load, with a statistically significant decrease observed on day 15 compared to the Nosema-infected group without supplementation (p < 0.001). A non-significant reduction in food consumption was also recorded in the N + BG groups. Malondialdehyde (MDA) levels decreased in a dose-dependent manner with increasing beta-glucan supplementation (p < 0.05). Furthermore, both beta-glucan concentrations (0.5 and 1%) significantly elevated glutathione (GSH) activity, glutathione peroxidase (GSH-Px), and catalase (CAT) levels (p < 0.05), with the 1% beta-glucan dose producing the greatest improvement in these antioxidant markers. In conclusion, beta-glucan supplementation effectively reduced N. ceranae spore load, improved survival and food consumption, alleviated oxidative stress as indicated by lower MDA levels, and enhanced antioxidant enzyme activities in infected honey bees. These results indicate that beta-glucan represents a promising dietary intervention to mitigate the adverse effects of Nosema infection.
Keywords: Antioxidant status; Apis mellifera; beta-glucan; food consumption; Nosema ceranae; spore counts; survival rate